Artificial intelligence in the politics of great powers: potential consequences to civil control of the military - Spasojević, Dušan (Sociološki pregled, 2025)
Today artificial intelligence permeates all the pores of social life, including international relations and security, where the attention of the professional public is primarily drawn in the context of armed conflicts and rivalry of great powers. Scientific research has not sufficiently considered the consequences of its use to civilian-military relations, although it is a key institutional component of defence policy and an important aspect of national security. This study uses the qualitative analysis of available data to monitor the process of the interaction of inherent characteristics of artificial intelligence and great powers0 politics, and by testing the existing theories, it explores why great powers uncritically place artificial intelligence in the function of security and how it will affect civilian-military relations. Moreover, this paper, in line with the already presented research question, analyzes some of the new security dilemmas, such as: military security of society turned outwards vs. internal values, ideologies and institutions. A brief historical context of the phenomenon and its definition determination prove to be indispensable in this example as well in the academic completion of the paper.
Keywords: artificial intelligence; international relations; security; defence policy; civil-military relations